Selective serotonin reuptake inhibitors in the treatment of depression: discontinuation and/or dependency syndrome? (Research, Society and Development, 2020)
Depression is a mental disorder that can affect people of any age group, of such complexity that it is necessary to have a specialist to evaluate and analyze each case, since it can be caused either by physiological changes or by external factors, or both. Concomitantly with psychological assistance, the use of antidepressants is indicated, with Selective Serotonin Reuptake Inhibitors (SSRIs) being the most used; therefore, the objective of this article is to discuss the effects of the discontinuation syndrome and/or dependence among SSRIs. A quantitative study of narrative bibliographic review was made using scientific articles from the last 16 years (2004-2020). The databases Medline, The Cochrane Library Database, Lilacs, PubMed, SciELO, Research Gate, Science Direct, PePSIC were used. The following terms were searched as descriptors: dependency syndrome, abstinence syndrome, depression, selective serotonin reuptake inhibitors, antidepressants and the Boolean AND. It is noted that doctors increasingly prescribe the use of SSRIs, as they have fewer side effects, but it is necessary to take precautions when dealing with drug interactions. For a person to become dependent on a substance, it is necessary to meet three of the six criteria established by the International Classification of Diseases (ICD-10) (1992), and, as discussed throughout the work, it does not occur with the correct use of antidepressants. However, the discontinuation syndrome can be caused by the rapid withdrawal of these drugs, requiring extra attention from the doctor at the end of treatment.